Performing feeling in cultures of memory - Trezise, Bryoni (Palgrave MacMillan, 2014)
This is one of the first studies to map conjunctions between memory culture, feeling and the performed nature of emotions. In using performance theory as the investigative framework for these interests, Bryoni Trezise argues that feelings occur as performed cultural effects. The study makes clear the often invisible cultural practices that link how we experience reconstructions of the past to how we produce emotional responses out of them. The book traverses site-specific, virtual, televisual and theatrical memory practices, which reach from Holocaust memorials, to the digital aesthetics of Second Life and the trauma spectacles exposed by reality TV or challenged by radical theatre. Drawing together recent discussions on emotion and the senses, she argues that memory in the new millennium is characterised by an 'experiential turn' that underscores relations between bodily behaviours and sentimental responses. Through these, Trezise rethinks the dominant models that shape and frame arguments for how and why we remember the pasts of others.